Cultural Meanings and Social Functions of Raw Shellfish Consumption in a Coastal Indonesian Community - Cian Ibnu Sina; Mila Abdullah; Syamilatul Khariroh; Ikha Rahardiantini; Wasis Pujiati; Ernawati (Social Impact Journal, 2025)
This study aims to uncover the unique coastal culture of the Riau Islands, namely the culture of processed raw shellfish. The habit of consuming processed raw shellfish is certainly familiar to both traditional and modern communities. Raw shellfish consumption is widely found in various places around the world, including Asia; for example, in Japan, there's sashimi; in Europe, specifically in Spain, there's ceviche de calamares; and in Korea, there's sannakji. The approach used in this study is a descriptive qualitative study with a specific case study of the culinary scene in Tanjung Bungsu Village, Resun Pesisir, North Lingga District, Lingga Regency, Riau Islands Province. This small village has inherited a distinctive coastal culture, with fishing as the primary livelihood of the local community in the Riau Islands region. The results of this study found a common practice of consuming raw shellfish made from various types of shellfish, especially clams (Tridacna gigas), mixed with natural spices and prepared traditionally. They call it bekasam, a fermented product made from raw shellfish.